2010
DOI: 10.1002/adfm.201001135
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembled Conjugated Thiophene‐Based Rotaxane Architectures: Structural, Computational, and Spectroscopic Insights into Molecular Aggregation

Abstract: A comparative study of the self‐assembly at a variety of surfaces of a dithiophene rotaxane 1⊂β‐CD and its corresponding dumbbell, 1, by means of atomic force microscopy (AFM) imaging and scanning tunneling microscopy (STM) imaging on the micrometer and nanometer scale, respectively. The dumbbell is found to have a greater propensity to form ordered supramolecular assemblies, as a result of π–π interactions between dithiophenes belonging to adjacent molecules, which are hindered in the rotaxane. The fine molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 59 publications
3
18
0
Order By: Relevance
“…1 × 10 −5 M solution) 38. As shown in Table 2, the ϕ PL of the synthesized PF copolymer is lower than that reported for a copolymer with PFO and electron‐donating TA moities,4 but similar with other reported results 22, 27, 29. However, we found that this shortcoming could be overcome by protecting the acceptor unit through its encapsulation into a macrocycle γCD molecule.…”
Section: Results and Discissionsupporting
confidence: 89%
See 2 more Smart Citations
“…1 × 10 −5 M solution) 38. As shown in Table 2, the ϕ PL of the synthesized PF copolymer is lower than that reported for a copolymer with PFO and electron‐donating TA moities,4 but similar with other reported results 22, 27, 29. However, we found that this shortcoming could be overcome by protecting the acceptor unit through its encapsulation into a macrocycle γCD molecule.…”
Section: Results and Discissionsupporting
confidence: 89%
“…Besides this, one should also consider as reason for higher ϕ PL the relocation of acceptor molecule into the more hydrophobic environment, which restricts rotational and vibrational motions and decreases the nonradiative decay pathways 40, 41. The enhanced ϕ PL can also be explained by a more planar and rigid structure of PF•γCD copolymer, which sterically prevents close contact between the aromatic cores and preserves single‐molecule photophysics for longer times after excitation 23, 29, 42…”
Section: Results and Discissionmentioning
confidence: 99%
See 1 more Smart Citation
“…[51] Among the varietieso fs mall molecular and polymerico rganic electrochromic materialsu sedi ne lectrochromic devices, oligothiophenesa sw ella s polythiophene derivatives area ni mportant classo fp-conjugated organic material. [52][53][54][55][56] Thiophene-based oligomersa nd polymers possess intrinsicc ontrasting colours between the neutral ando xidized forms concomitantw ithf orming stable intermediates. [57][58][59][60] Moreover,polythiophenese xhibits everal additionaladvantagesi ncluding well definedm olecular backbone,s olution processability,p recise molecular ordering andc rystallinityf or superior charge transfer.T he molecular structurei sakeyf actorf or molecularp acking induced by severaln on-covalenti nteractions, whichi nfluence the morphology of materials.…”
Section: Introductionmentioning
confidence: 99%
“…This possibility represents an attractive approach to achieve control over molecular rigidity, prevention of aggregation, improved PLQE, and surface‐morphological characteristics of the resulting conjugated polyrotaxanes. Macrocyclic encapsulation of conjugated monomers into native cyclodextrins (CDs), as macrocycle host molecules followed by polymerization has been employed as an alternative supramolecular approach to achieve an “insulation” of the individual molecular wires . Such threading of macrocycles onto the conjugated chains does not disrupt the π‐conjugation and can additionally improve the solubility as well as the morphological characteristics of the resulting polymers.…”
Section: Introductionmentioning
confidence: 99%